Artist Talk/Lecture Presentation Settlements: Mountains Upside Down - Pericleous, Vicky; Neokleous, Dimitris; Karambambas, Stephanos; Kallis, Kyriakos (My University, 2023)
The workshop/seminat/seminar is expected to: Bring together artists, cultural institutions and key thinkers in creative sustainability, philosophy and social sciences to discuss and explore ways of intensifying the powers of art in tackling the key pillars of sustainability. Introduce, discuss and clarify the meaning of "empathy" in arts, which has important implications for artistic research, training and practice. Clarify and demonstrate how empathy as an abstract concept can be applied in the arts so that people are motivated to care for non-human others and the environment by using concrete examples. Support artists and cultural professionals to engage with mainstream research from philosophy, social sciences and sustainability studies on the role of empathy and perspective-taking in advocating for environmental issues.
Keywords: Arts